Pengembangan Bahan Ajar E-Modul Sistem Reproduksi Manusia Menggunakan Aplikasi Flip PDF Corporate - Sugianto Sugianto; Angreni Beaktris Liunokas; Nening Listari; Ni Putu Yuni Astriani Dewi; Abdur Rasyid; Diki Muahamad Chaidir (Postgraduate, University of Mataram, 2023)
This research focuses on developing and implementing e-module teaching materials for the human reproductive system using the Flip PDF Corporate application. Following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the study begins with an analysis of student and teacher needs, along with an examination of the human reproductive system's basic competencies. The resulting e-module structure includes sections such as Introduction, Human Reproductive System overview, and Closing, among others. Expert validation, involving biologists and digital media experts, contributes to the development process. The study's implementation results indicate positive outcomes, with an average test score of 79.50, surpassing the KKM standard, and a good classification value. All students passed, with 53% achieving a good grade and 47% reaching a very good grade. Student responses also highlight the favorable material and technical quality aspects of the Flip PDF Corporate application. Overall, the research successfully demonstrates the effectiveness of the designed teaching materials for the human reproductive system.